Threat of a Cycle Proof: Vertebral Artery Dissection Associated with Posterior Inferior Cerebellar Artery Infarction - Francisco Monteiro; Pedro Oliveira; Artur Condé (Case Reports in Otolaryngology)
This paper presents a case of a perfectly healthy 36-year-old male, who went to the emergency department with a clinical picture of diffuse headache, dizziness, and asthenia with 3 days of evolution, after a long cycling race. He was admitted to the ENT Department with suspected diagnosis of peripheral vertigo. The patient developed hypoesthesia of the face, diplopia, right lateropulsion, and Romberg with preferential rightward fall, and imaging studies demonstrated an extracranial vertebral artery dissection concomitant with PICA territory infarction. This is a rare described case of a vertebral artery dissection concomitant with an infarction of the PICA territory. This case demonstrates the importance of maintaining a high degree of suspicion of stroke in patients with signs/symptoms of nystagmus/vertigo and the relevance of magnetic resonance imaging instead of tomography in the detection of these serious clinic conditions.